2007
DOI: 10.1111/j.1537-2995.2007.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate can replace fetal bovine serum for clinical‐scale expansion of functional mesenchymal stromal cells

Abstract: Replacing FBS with HPL prevents bovine prion, viral, and zoonose contamination of the stem cell product. This new efficient FBS-free two-step procedure for clinical-scale MSC propagation may represent a major step toward challenging new stem cell therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
396
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 452 publications
(434 citation statements)
references
References 46 publications
27
396
2
9
Order By: Relevance
“…Because anti-FCS antibodies with uncertain clinical significance could be detected in patients after receiving MSC that were expanded in vitro using FCS, 20 we decided for safety reasons to replace FCS by platelet lysates. 17 In addition, compared with our series, the MSC dosage tended to be higher with a median of 1 Â 10 6 /kg (range 0.7-9 Â 10 6 per kg) and nine patients received only one or two MSC infusions in our cohort. Another publication reported a complete disappearance of GVHD symptoms in five of six patients (83%) after receiving adipose tissue-derived MSC.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because anti-FCS antibodies with uncertain clinical significance could be detected in patients after receiving MSC that were expanded in vitro using FCS, 20 we decided for safety reasons to replace FCS by platelet lysates. 17 In addition, compared with our series, the MSC dosage tended to be higher with a median of 1 Â 10 6 /kg (range 0.7-9 Â 10 6 per kg) and nine patients received only one or two MSC infusions in our cohort. Another publication reported a complete disappearance of GVHD symptoms in five of six patients (83%) after receiving adipose tissue-derived MSC.…”
Section: Discussionmentioning
confidence: 92%
“…The first MSC infusion was given at a median of 41 days (range 20-91) after transplantation, donor lymphocyte infusion or cessation of immunosuppression and 16 days after the onset of aGVHD (range 4-31). The median number of MSC transfusion was 2 (range 1-5), the median interval between each MSC application was 7 days (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and the average MSC dose given was 0.9 Â 10 6 per kg body weight (range 0.6-1.1 Â 10 6 per kg body weight) (Table3 and Figure 3). No infusion-related toxicity was observed during or immediately after the administration of MSC.…”
Section: Clinical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is being established as a safe and efficient MSC culture supplement for robust MSC cultivation, thus offering certain advantages as potential FBS substitutes (18)(19)(20)(21). Analyses of platelet lysates, and subcellular fractions have shown that numerous bioactive molecules are stored within distinct platelet organelles including adhesive proteins, coagulation factors, mitogens, protease inhibitors, and proteoglycans (22).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…The most commonly used animal product in cell culture is foetal calf serum; this could pose a risk of cross-contamination, induce an immune response, or be an infection risk [37]. There is great interest in developing alternatives to calf serum to avoid these problems such as culturing the cells in the patient's own serum [37,55,102] or using human platelet lysate as an alternative [100]. hESC are commonly cultured on a layer of murine feeder cells which at present together with issues of histocompatability restricts their clinical use currently.…”
Section: Expansion Of Cell Number and In Vitro Culturementioning
confidence: 99%